Development of Information System for Wood-Based Industries in Ekiti State, Nigeria. (2017)
Development of information system in forestry sector is crucial in order to manage resources in a sustainable manner. Spatial distribution of forest and wood-based industries is important for sustainability. However, geographic location and other information about the wood-based industries in Ekiti state, which can provide baseline information for investors in wood industry, are dearth. To proffer solution to this, information system was developed for wood-based industries in the State using geographic information system. This was done by taking the coordinates and photographs of all wood-based industries in the State. Types of equipment used for different wood conversion were assessed with the aim of determining their strength and capacity. The photographs and coordinates were loaded into ArcView GIS for analysis. The wood-based industries were represented on the State map using their coordinates while respective pictures were hotlinked appropriately. Various local governments in the State were represented with polygons of different sizes and wood industries were represented with points. The results obtained from the analysis were used to produce database in MS SQL server. The database created by Microsoft SQL server formed the data access (back end) of the software developed using C# Programming Language. Appropriate codes were written at the business logic layer for both the back and the front ends. The software was developed in an Interactive Development Environment (IDE) using visual studio. It was observed that most of the wood-based industries were concentrated at the southern part of the State where there were more forest reserves. Gbonyin Local Government has the highest number of wood industry (46) while Efon Local Government has none at all. Over 95% of the existing wood industry was functioning with 91% of them using CD6 machine. The software developed is user-friendly, facilitates efficient data storage and prompt information retrieval, adequate and has provision for regular updates.